Metronidazole Modified-Release Therapy Using Two Different Polymeric Systems Gels or Films: Clinical Study for the Treatment of Periodontitis - Mônica Danielle Ribeiro Bastos; Tatiane Cristina Dotta; Beatriz Roque Kubata; Cássio do Nascimento; Ana Paula Macedo; Fellipe Augusto Tocchini de Figueiredo; Millena Mangueira Rocha; Maria Paula Garofo Peixoto; Maíra Peres Ferreira; Osvaldo de Freitas; Vinicius Pedrazzi (MDPI AG, 2024)
This study evaluated the efficacy of semisolid systems (gels) and films containing a combination of metronidazole (MTZ) and metronidazole benzoate after scaling and root-planing (SRP) for periodontitis. In total, 45 patients with stage I or II periodontitis were enrolled and divided into 3 groups: 1-SRP-control; 2-SRP + Film with MTZ; 3-SRP + Gel with MTZ. The pH of gingival crevicular fluid (GCF) before/after treatments, MTZ concentrations, and drug release using high-performance liquid chromatography were investigated. The effects were evaluated by longitudinal monitoring of clinical parameters (probing depth-PD, clinical attachment level-CAL, and bleeding on probing-BP). MTZ and MTZ-benzoate concentrations in the periodontal pocket and pH showed no statistical difference after application. SRP + Gel presented the lowest CAL values. For SRP + Film and SRP + Gel, higher PD values were observed at T0 compared to all groups. A relevant reduction in BP was observed in SRP + Film and SRP + Gel groups at all times compared to T0. Both therapies improved periodontal health compared to SRP alone, reducing PD and BP, and increasing CAL for the gel group, suggesting they are promising for periodontal disease treatment.